Paul Bénichou : Selon Mallarmé. Gallimard, Paris, 1995. 420 p. - Serge Meitinger : Stéphane Mallarmé. Hachette, coll. «Portraits littéraires», Paris, 1995. 280 p. - Lund, Hans Peter (Revue Romane, 1996)
-